PERAN PARTAI POLITIK LOKAL DALAM PENYELANGGARAAN OTONOMI KHUSUS DI ACEH - M. Fahrudin Andriyansyah (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2020)
AbstactAs a national organization, political parties are considered to have failed in carrying out their roles and functions, especially in the implementation of regional autonomy. The existence of political parties that are only national in nature with structures centered in the center often makes the party's orientation ignore local interests. The neglect was due to the institutionalization of political parties so far as merely structuring relations. This pattern positions politicians in political parties in the region as subordinates of the same party politicians at the national level. The failure of political parties in the implementation of regional autonomy can be interpreted as necessary to regulate a new party system in Indonesia. One of them is by separating between national political parties and local political parties in the regions. This means that with the policy of regional autonomy, it must be accompanied by political autonomy through local political parties. Therefore this study will look at the role of local political parties that have existed in Aceh in the implementation of special autonomy and at the same time see whether local political parties have played a role or not in the implementation of special autonomy in Aceh. Local political parties, especially the Aceh Party in 2014 obtained the highest number of seats in the Aceh People's Representative Council (DPRA) compared to national political parties, so the Aceh Party had a strategic position as the leader of the DPRA and the leadership of a number of DPRA equipment. The role of local political parties can be seen through the role of the faction of local political parties in the DPRA, especially the Aceh Party faction, which is related to the role of legislation, budgeting and Controling. The Aceh Party faction has played a role in organizing special autonomy in Aceh AbstrakSebagai organisasi yang bersifat nasional, partai politik dirasa telah gagal dalam menjalankan peran dan fungsinya, terutama di dalam penyelenggaraan otonomi daerah. Keberadaan partai politik yang hanya bersifat nasional dengan struktur yang berpucuk di pusat kerap kali membuat orientasi partai mengabaikan kepentingan lokal. Pengabaian itu dikarenakan pelembagaan partai politik selama ini dimaknai sebagai hubungan strukturalisasi semata. Pola ini memposisikan politisi partai politik di daerah sebagai sub ordinat politisi partai yang sama di tingkat nasional. Tidak berjalannya partai politik dalam penyelengaraan otonomi daerah dapat dimaknai bahwa perlu untuk mengatur sistem kepartaian baru di Indonesia. Salah satunya adalah dengan melakukan pemisahan antara partai politik nasional dengan partai politik lokal yang ada di daerah. Artinya dengan adanya kebijakan otonomi daerah maka harus dibarengi dengan adanya otonomi politik melalui partai politik lokal. Oleh karena itu penelitian ini akan melihat peran partai politik lokal yang telah ada di Aceh dalam penyelenggaraan otonomi khusus sekaligus melihat apakah partai politik lokal telah berperan atau tidak di dalam penyelenggaraan otonomi khusus di Aceh. Partai politik lokal terutama Partai Aceh pada tahun 2014 memperoleh jumlah kursi terbanyak di Dewan Perwakilan Rakyat Aceh (DPRA) dibandingkan dengan partai politik nasioanal, sehingga Partai Aceh memiliki posisi strategis sebagai pimpinan DPRA dan pimpinan sejumlah alat kelengkapan DPRA. Peran partai politik lokal dapat dilihat melalui peran Fraksi Partai politik lokal yang berada di DPRA terutama Fraksi Partai Aceh, yaitu berkaitan dengan peran legislasi, anggaran (budgeting) dan pengawasan (Controling). Fraksi Partai Aceh telah berperan dalam penyelenggaran otonomi khusus di Aceh.Kata Kunci: Partai Politik Lokal, Otonomi Khusus, Partai Aceh, DPRA